Mesenchymal stem cell therapy for pulmonary hypertension: an update - Tian, Renmei; Xu, Shangfu; Liu, Chan; Wang, Yuying; Wu, Yutong; Li, Lisheng; Liu, Juan (Frontiers in Bioengineering and Biotechnology, 2025)
Pulmonary Hypertension (PH) is a life-threatening condition characterized by pulmonary vascular remodeling. Without treatment, it may progress to right heart failure, the main cause of death in such cases. Although traditional drugs can slow PH progression, their efficacy is often limited, underscoring an urgent need for new treatments. Stem cell therapy, meanwhile, has emerged as a promising approach for various refractory diseases, with considerable therapeutic potential. This article reviews preclinical findings on mesenchymal stem cell (MSC) therapy for PH, focusing on how MSCs alleviate right ventricular failure, reverse pulmonary arterial smooth muscle cell proliferation, restore endothelial function, and regulate anti-inflammatory factor expression. It also discusses the therapeutic effects of MSC-derived exosomes. The current challenges and future perspectives of MSCs in clinical applications are also explored. Preclinical studies suggest that MSCs hold considerable promise for treating PH. However, further studies are needed to clarify the mechanisms behind their therapeutic effects and develop strategies for the safe, efficient large-scale production of MSCs for clinical use.